2021
DOI: 10.1177/15330338211062415
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam CT (CBCT) Based Synthetic CT Generation Using Deep Learning Methods for Dose Calculation of Nasopharyngeal Carcinoma Radiotherapy

Abstract: Objective: To generate synthetic CT (sCT) images with high quality from CBCT and planning CT (pCT) for dose calculation by using deep learning methods. Methods: 169 NPC patients with a total of 20926 slices of CBCT and pCT images were included. In this study the CycleGAN, Pix2pix and U-Net models were used to generate the sCT images. The Mean Absolute Error (MAE), Root Mean Squared Error (RMSE), Peak Signal to Noise Ratio (PSNR), and Structural Similarity Index (SSIM) were used to quantify the accuracy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…The most objective comparisons of image quality can be found in studies that compare multiple architectures or correction techniques for generating sCT images using the same datasets. 18,19,27,35,39,41,44,47,49,57,60,61,63 Where DL methods were compared to classical CBCT correction methods, Barateau et al 61 demonstrated that their GAN sCT achieved a lower MAE than DIR of the CT (82.4 ± 10.6 vs. 95.5 ± 21.2 HU), which was found to be consistent with the results in Thummerer et al (36.3 ± 6.2 vs. 44.3 ± 6.1 HU). 57 Similarly in Liang et al, 39 cycle-GAN showed improved image qual-ity metrics over DIR of the CT when a saline-adjustable phantom was used in a controlled experiment.…”
Section: Network Architecturessupporting
confidence: 70%
See 3 more Smart Citations
“…The most objective comparisons of image quality can be found in studies that compare multiple architectures or correction techniques for generating sCT images using the same datasets. 18,19,27,35,39,41,44,47,49,57,60,61,63 Where DL methods were compared to classical CBCT correction methods, Barateau et al 61 demonstrated that their GAN sCT achieved a lower MAE than DIR of the CT (82.4 ± 10.6 vs. 95.5 ± 21.2 HU), which was found to be consistent with the results in Thummerer et al (36.3 ± 6.2 vs. 44.3 ± 6.1 HU). 57 Similarly in Liang et al, 39 cycle-GAN showed improved image qual-ity metrics over DIR of the CT when a saline-adjustable phantom was used in a controlled experiment.…”
Section: Network Architecturessupporting
confidence: 70%
“…The greatest disparity was observed between cycle-GAN and U-Net (51.0% vs. 36.8% respectively, p = 0.37), 18,19,41 whereas a smaller difference was noted between cycle-GAN and GAN networks (58.3% vs. 51.5% respectively, p = 0.24). 18,19,39,49…”
Section: Network Architecturesmentioning
confidence: 85%
See 2 more Smart Citations
“…Xue et al. implemented three deep learning models, CycleGAN, Pix2pix, and UNet, for synthetic CT generation from onboard CBCT images 11 . All of the models achieved better evaluation metrics based on the DVH and 2D gamma index analysis.…”
Section: Introductionmentioning
confidence: 99%